Profile of Fluoride Release from a Nanohybrid Composite Resin - Raquel Assed Bezerra Silva; Fernanda Regina Ribeiro Santos; Augusto Cesar Cropanese Spadaro; Ana Cristina Morseli Polizello; Andiara De Rossi; Marilia Rodrigues Moreira; Paulo Nelson-Filho (University Library System, University of Pittsburgh, 2015)
The aim of this study was to evaluate in vitro the amount and profile of fluoride release from a fluoride-containing nanohybrid composite resin (Tetric® N-Ceram) by direct potentiometry. Thirty specimens (5 mm diameter x 3 mm high; n=10/material) were made of Tetric® N-Ceram, Vitremer® resin-modified glass ionomer cement (RMGIC) (positive control) or Filtek® Z350 nanofill composite resin (negative control). The specimens were stored individually in plastic tubes containing 1 mL of artificial saliva at 37°C, which was daily renewed during 15 days. At each renewal of saliva, the amount of fluoride ions released in the solution was measured using a fluoride ion-selective electrode with ion analyzer, and the values obtained in mV were converted to ppm (µg/mL). Data were analyzed statistically by ANOVA and Tukey's post-hoc test at a significance level of 5%. The results showed that the resins Tetric® N-Ceram and Filtek® Z350 did not release significant amounts of fluoride during the whole period of evaluation (p>0.05). Only Vitremer® released significant amounts of fluoride ions during the 15 days of the experiment, with greater release in first 2 days (p<0.05) and stabilization in the subsequent days (p>0.05). In conclusion, the nanohybrid composite resin Tetric® N-Ceram did not present in vitro fluoride-releasing capacity throughout the 15 days of study.